The Impact of Thematic Learning Integrated ICT in Tabot Bengkulu as Cultural Ceremony toward Social Interaction Knowledge in Elementary School - WINARNI, Endang Widi; PURWANDARI, Endina Putri; LUSA, Herman; DADI, Sri (Asian Journal of Education and Training, 2018)
Tabot Bengkulu as one of cultural ceremony in Bengkulu province is a cultural asset that held once a year in Muharram Month in Islamic Calendar. This ceremony has many character values in society such as religious, social care, and environment care. The use of local wisdom in learning can improve the social interaction knowledge for elementary students. The purpose of this research is to determine the impact of integrating ICT with thematic learning and discovery learning model for tabot Bengkulu as a cultural ceremony toward social interaction knowledge in elementary school. The research implemented pretest-posttest control group design. The research populations are two classes of fourth-grade students from the elementary school in Bengkulu in the academic year 2017-2018. These classes are divided into two, one class from as the experiment group with discovery learning and ICT from state elementary school 1 and the other one class as the control group with conventional media from state elementary school 22. The instrument used to measure student knowledge about the uniqueness of my residence area. The results showed that the average score difference between posttest and pretest in the control group was 23.46 and in the experimental group of 38.12 The analysis results for t value 0.13 and t table 2.00. It can be concluded that there is no significant effect of thematic learning based on the potential of the region with the discoveries of learning and ICT media on the knowledge of elementary students about the cultural ceremony "Tabot Bengkulu".